Systemic Barriers and Strategic Solutions in Waste Governance - Nasriani, Ira (Sinergi International Journal of Accounting and Taxation, 2024)
This narrative review investigates the synergistic role of social, economic, and institutional factors in influencing the success of sustainable waste management strategies. The study aims to explore how the interaction of these multidimensional variables can either facilitate or hinder the implementation of effective environmental policies. Using a qualitative synthesis of peer-reviewed literature, the review integrates empirical findings and theoretical frameworks to identify thematic patterns and systemic barriers. The results reveal that while social engagement and community-based collaboration enhance policy acceptance and operational cohesion, economic factors such as funding availability, investment in green technology, and fiscal incentives critically determine policy feasibility. At the institutional level, transparency, coordination, and the adoption of non-financial performance evaluation methods significantly strengthen governance frameworks. However, persistent challenges such as fragmented regulations, resistance to technology adoption, and inadequate inter-agency communication continue to undermine policy success. The discussion emphasizes the need for integrative strategies that bridge these dimensions through cross-sectoral collaboration, digital innovation, and participatory governance. Ultimately, the findings advocate for a shift from reactive, siloed policymaking to proactive, system-level interventions that address structural constraints. This study offers strategic recommendations and a conceptual foundation for future research and policymaking aimed at promoting holistic, resilient, and scalable sustainability practices.